EXPLORING GREEN PURCHASE INTENTION USING A SYSTEMATIC LITERATURE REVIEW - Maria Cempaka Putri Wijayanto; Elisabet Dita Septiari (International Journal of Economics, Business and Accounting Research (IJEBAR), 2026)
This study presents a systematic literature review on green purchase intention behaviour. From an initial pool of 26 journals, 16 were selected for in-depth analysis. The review reveals that most studies adopt the Theory of Planned Behaviour (TPB). Online survey methods and PLS-SEM were commonly employed for data collection and analysis. The findings show that environmental self-identity and positive attitudes toward eco-friendly products are the strongest predictors of green purchase intention, while personal norms and value-driven motivations also play significant roles. Sociodemographic factors, such as age, gender, and cultural background, are identified as important moderators. Future research should consider incorporating the Self-Determination Theory (SDT) to explore intrinsic and extrinsic motivations, the Protection Motivation Theory (PMT) to assess the role of perceived environmental threats, and the Diffusion of Innovations Theory (DOI) to examine adoption patterns based on consumer categories. Expanding research to cross-national contexts and integrating broader socio-cultural variables could further enhance understanding. This synthesis provides valuable insights for researchers in designing effective strategies to promote environmentally friendly purchasing decisions.